2014
DOI: 10.3944/aott.2014.3014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of primary bone lymphoma and the importance of positron emission tomography

Abstract: Primary lymphoma of the bone is an extremely rare tumor in the form of non-Hodgkin lymphoma or Hodgkin lymphoma. The majority of primary bone lymphomas are non-Hodgkin lymphoma, of which the most common subtype is diffuse large cell lymphoma. Patients can present with pain, swelling or pathologic fracture. Definitive diagnosis is made after biopsy examination. Treatment consists of chemotherapy, radiotherapy and surgery. We report 3 male patients who presented with pain and swelling. Involvement was in the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…[ 61 ] Alper et al reported in a young male diagnosed with primary bone lymphoma located in distal femur, distal femoral resection prosthesis was performed to prevent the risk of fracture and the patient was in remission and continued to attend school. [ 60 ] From the CT scan of our patient, we can see that the ilium, acetabular, and sacroiliac joint are severe destructed making the patient meet high risk of pathologic fracture. Furthermore, the patient showed a sciatic nerve comprehension symptom which was confirmed during surgery procedure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 61 ] Alper et al reported in a young male diagnosed with primary bone lymphoma located in distal femur, distal femoral resection prosthesis was performed to prevent the risk of fracture and the patient was in remission and continued to attend school. [ 60 ] From the CT scan of our patient, we can see that the ilium, acetabular, and sacroiliac joint are severe destructed making the patient meet high risk of pathologic fracture. Furthermore, the patient showed a sciatic nerve comprehension symptom which was confirmed during surgery procedure.…”
Section: Discussionmentioning
confidence: 96%
“…[ 45 ] For bony HL, surgery was necessary for the treatment of actual or possible pathological fractures or spine cord and nerve comprehension. [ 52 , 59 , 60 ] Limb-salvage surgery in some special individuals got a satisfying clinical outcome. In a large series study, Khodamorad and colleagues suggested that combined-modality therapy for stage IE primary bone lymphoma resulted in good survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic samples obtained by surgical procedure and immunohistochemical tests are indispensable for clinicoradiological confirmation of PBL and for differential diagnosis. Other surgical procedures, especially excision of lesions, should be avoided whenever possible, unless the involved weight-bearing bones are destroyed extensively or pathological fractures are present in bone lesions [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Other surgical procedures, especially excision of lesions, should be avoided whenever possible, unless the involved weight-bearing bones are destroyed extensively or pathological fracture is present in bone lesions. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%